Material de Referencia Piloto: Nutrientes en leche en polvo - IVONNE ALEJANDRA GONZALEZ CARDENAS; ANDRES MAURICIO CASTILLO FORERO; SILVIA LORENA RAMIREZ MARIN; KEVIN ADRIAN VILLALOBOS CARDENAS; JULIANA SERNA SAIZ; Serna Saiz, Juliana; González Cárdenas, Ivonne Alejandra; Castillo Forero, Andres Mauricio (Instituto Nacional de Metrología - INM, 2020)
Material de Referencia Piloto: Nutrientes en leche en polvo